Medium-term evolution of an intermediate beach with an intertidal bar (Amoreira beach, Southwest Portuguese rocky coast) - Gama, C. (2020)
The subaerial beach and low tide terrace morphology of the Amoreira beach (Southwest Portuguese Coast) was assessed using a DGPS system between December 2006 and October 2008. The offshore wave conditions were described by the SWAN model, and the nearshore wave using the COULWAVE model. DEMs show significant variations on beach width and berm elevation, and intertidal bar migration. The seasonal variation of the beach width (from the 2 m contour line above the MSL to the dune baseline) is significant (88 to 66 m) indicating a subaerial beach retreat of 13 m. The berm height elevation ranges between 3.3 and 2.5 m. The obtained results also show that beach sedimentary budget results from a close relationship between the volumes of sediment retained on the subaerial beach (mainly the width variations) and the morphology of the intertidal bar. The effect of intertidal bar morphology variations on the wave height for the field surveys of 6th April and 18th October 2008 was analysed. The obtained data set indicates that: 1) the intertidal bar migrated in the landward direction welding to the beachface lower limit by infilling a runnel of -0.61 m (minimum elevation); 2) the frontal berm increased the width and elevation in 8 m and 0.7 m, respectively; 3) the intertidal bar morphology with a trough on its landward side allows the dissipation of about 0.029 kJm-2/m of the wave energy along the surf zone; and 4) the wave spectrum shows a frequency band between 0.03 and 0.35 Hz.